Yusuf Qardhawi's Thoughts in Contemporary Fiqh on Professional Zakat - Ariibah Radita Ayu Candrika; Kurnia Nur Aliffia; Nafidatun Nisa; Lutfiyah, Lutfiyah (al-Afkar, Journal For Islamic Studies, 2025)
Professional zakat is a form of zakat legal development that adjusts to the development of the modern economy, where most of the income is obtained from the professional sector. Yusuf Qardhawi argues that professional zakat must be issued like agricultural and trade zakat, with the principle of justice and the benefit of the people. The purpose of this study is to provide insight into Yusuf Qardhawi's thinking in contemporary fiqh issues, especially on professional zakat issues. This type of research uses a library research method that relies on literature reviews and several other sources. The results of the study show that Yusuf Qardhawi's ideas make an important contribution to the development of zakat fiqh that is more adaptive to the needs of the times. This research is expected to provide a broader understanding of the concept of professional zakat in the modern Islamic economic system.